Clinical and Molecular Epidemiology of Childhood Invasive Nontypeable Haemophilus influenzae Disease in England and Wales. Issue 3 (March 2016) - Collins, Sarah; Vickers, Anna; Ladhani, Shamez N.; Flynn, Sally; Platt, Steven; Ramsay, Mary E.; Litt, David J.; Slack, Mary P. E.
Abstract : Introduction: In countries with established Haemophilus influenzae type b (Hib) immunization programs, nontypeable H. influenzae (NTHi) is now responsible for nearly all invasive H. influenzae cases across all age groups. Methods: Public Health England (PHE) conducts enhanced national surveillance of invasive H. influenzae disease in England and Wales. Invasive NTHi isolates submitted to Public Health England from children of ages 1 month to 10 years during 2003–2010 were characterized by multilocus sequence typing (MLST). Detailed clinical information was obtained for all laboratory-confirmed cases of invasive NTHi disease in children during 2009–2013. Results: In England and Wales, there were 7797 cases of invasive H. influenzae disease diagnosed during 2000–2013 and 1585 (20%) occurred in children aged 1 month to 10 years, where NTHi was responsible for 31–51 cases (incidence, 0.53–0.92/100, 000) annually. Detailed clinical follow-up of 214 confirmed NTHi cases diagnosed in this age-group during 2009–2013 revealed that 52% (n = 111) occurred in <2-year-old and 52% (n=110) had comorbidity. Bacteremic pneumonia was the most common clinical presentation (n = 99, 46%), 16% (n = 34) required intensive care and 11% (n = 23) died. Characterization by biotyping and MLST of 316 NTHi strains from children with invasive disease during 2003–2010 revealed a genetically heterogeneous population (155 MLSTs) with diverse biotypes and no association with comorbidity status, clinical disease or outcome. Conclusions: The high level of genetic diversity in invasive NTHi strains highlights the difficulties in developing an effective vaccine against this pathogen.